2008
DOI: 10.1073/pnas.0710711104
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature predicts sex ratios and male longevity

Abstract: The theory that natural selection has conserved mechanisms by which women subjected to environmental stressors abort frail male fetuses implies that climate change may affect sex ratio at birth and male longevity. Using time series methods, we find that cold ambient temperatures during gestation predict lower secondary sex ratios and longer life span of males in annual birth cohorts composed of Danes, Finns, Norwegians, and Swedes born between 1878 (earliest year with complete life tables) and 1914 (last birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
105
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 19 publications
10
105
3
Order By: Relevance
“…Elucidation of potential pathways (e.g., temperature change 20 causing maternal inhalation during pregnancy of smoke or particulate matter from coal-burning stoves) would also inform whether developmental plasticity (Strand, Barnett & Tong, 2011;Barker, 1998) or selection in utero (Catalano, Bruckner & Smith, 2008) best describes our pattern of results. Whereas the failure to observe male-specific reactivity detracts from the male-specific culling argument, Uppsala births from 1915 to 1929 may have experienced less selection pressure in utero than the 18 th and 19 th century Swedish populations examined in previous studies (Catalano, Bruckner & Smith, 2008, Catalano et al, 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elucidation of potential pathways (e.g., temperature change 20 causing maternal inhalation during pregnancy of smoke or particulate matter from coal-burning stoves) would also inform whether developmental plasticity (Strand, Barnett & Tong, 2011;Barker, 1998) or selection in utero (Catalano, Bruckner & Smith, 2008) best describes our pattern of results. Whereas the failure to observe male-specific reactivity detracts from the male-specific culling argument, Uppsala births from 1915 to 1929 may have experienced less selection pressure in utero than the 18 th and 19 th century Swedish populations examined in previous studies (Catalano, Bruckner & Smith, 2008, Catalano et al, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Catalano and colleagues offer a different explanation of how temperature in utero may affect mortality later in life, especially among males (Catalano, Bruckner & Smith, 2008). They assert that cold during gestation selects especially against male fetuses least adapted to prevailing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In humans oscillations in ambient temperature are also associated with greater mortality in adults (Basu and Samet 2002;Lerchl 1998;Young and Mäkinen 2010) and predict the survivability of new-borns, with both increases (Catalano et al 2008) and decreases (Young and Mäkinen 2010) negatively associated with survival during the first year of childhood (Catalano et al 2008(Catalano et al , 2012Young and Mäkinen 2010). These effects appear to be more pronounced for males than females and thus it is argued that climatic shifts cause gestational stress that affects sex allocation in humans (Catalano 2011;Catalano et al 2008;Helle et al 2008Helle et al , 2009Navara 2009). Indeed, variation in environmental factors such as climate, ambient temperature and rainfall appear to predict fluctuations in the human SSR, with more males being born within more favourable ecological conditions (Catalano et al 2008;Helle et al 2009).…”
Section: Introductionmentioning
confidence: 95%
“…Time-series analyses conducted within subarctic climates of Finland and across Scandinavia using long-term historical datasets demonstrated that more males are born in years with relatively higher annual mean temperatures (Catalano et al 2008;Helle et al 2008Helle et al , 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation